2018
DOI: 10.26630/jk.v9i2.947
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberian Konseling Gizi terhadap Penurunan Kadar Kolesterol Darah

Abstract: Impact of Nutritional Counseling in Reducing Blood Cholesterol. Technological and socioeconomic advances resulted in dietary changes from the traditional diet to the western diet such as high-calorie fast food and fat, thus impacting the high prevalence of cholesterol in the community. One effort to reduce blood cholesterol can be done through consultation or counseling with a nutritionist. The study aimed to measure the effect of nutritional counseling on the decrease of cholesterol. This quasi-experimental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 7 publications
0
2
0
12
Order By: Relevance
“…This is different from other studies which concluded that there was a significant influence on the provision of nutritional counseling using the media and without the media. The counseling is carried out twice a week to reduce patients' blood cholesterol levels in the Banda Aceh City Health Center 15 .…”
Section: Resultsmentioning
confidence: 99%
“…This is different from other studies which concluded that there was a significant influence on the provision of nutritional counseling using the media and without the media. The counseling is carried out twice a week to reduce patients' blood cholesterol levels in the Banda Aceh City Health Center 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Begitu juga menurut Ades et al (2001), terkait olahraga yang dikombinasikan dengan konseling nutrisi telah menunjukkan bahwa perlambatan aterosklerosis dan penurunan angka kejadian koroner lanjutan dan rawat inap. Menurunkan kadar kolesterol serta High Density Lipoprotein (HDL) dan LDL, tidak harus dengan menggunakan obat obatan, tetapi dapat dilakukan dengan berkonsultasi/konseling kepada ahli gizi atau dengan meng-gunakan metode berolahraga (Al Rahmad, 2018). Aktifitas fisik mempunyai kontribusi positif dalam membentuk indeks masa tubuh (IMT) yang ideal (Candrawati, 2011).…”
Section: Pendahuluanunclassified
“…Leaflet dapat diberikan atau disebarkan pada saat pertemuan-pertemuan dilakukan seperti FGD (Focus group discussions), pertemuan posyandu,kunjungan rumah dan lainlain. Leaflet dapat dibuat sendiri dengan di perbanyak seperti photo copy (Al Rahmad, 2018).…”
Section: Pendahuluanunclassified